Analysis of Polybrominated Biphenyls in Environmental Samples by Porous Anodic Alumina-Based Solid-Phase Microextraction Combined with Gas Chromatography - Lv, Mengyu; Chang, Rui; Zhao, Guangchao (Asian Journal of Chemistry, 2015)
Porous anodic alumina was fabricated as solid-phase microextraction fiber coating by a two-step anodization process. The obtained coating presents a regular nanoporous array structure with pore diameter of 60 nm, characterized with scanning electron microscopy. It was employed in analysis of polybrominated biphenyls (PBB 9, 30, 52, 103 and 155) followed by gas chromatography detection. Key parameters affecting extraction procedures, including extraction temperature, time, salt concentration and desorption time, were optimized. Under the optimal conditions, the calibration curves were linear within the range of 0.05-3 μg/L and the detection limits were between 0.006 and 0.013 μg/L. The single fiber and fiber-to-fiber relative standard deviations were below 8.2 and 11.3 %, respectively. Finally, the developed method was applied to the analysis of polybrominated biphenyls in real samples and the reliability of method was proved by recovery experiments.